Abnormal Methylation Status of the GNAS Exon 1A Region in Pseudohypohyperparathyroidism Combined With Turner Syndrome. (December 2015) - Zhu, Jie; Wang, Dong; Ren, An; Xing, Yan; Zhang, Dongliang; Wei, Jun; Yu, Ning; Xing, Xuenong; Ye, Shandong
Abstract : Abstract: Pseudohypohyperparathyroidism (PHHP) is a rare type of pseudohypoparathyroidism (PHP), which seems to have a normal skeletal response to parathyroid hormone but shows renal resistance. Almost all patients with PHHP have PHP Ib, a subtype of PHP that is usually caused by GNAS methylation defects, often in exon 1A. Some features of Albright hereditary osteodystrophy can occasionally be found in patients with PHHP, but these features are also common in Turner syndrome. The authors report on an extremely rare case of a patient with PHHP and Turner syndrome, a 47-year-old woman who sought medical attention for hypocalcemia and elevated parathyroid hormone. She had no family history of hypocalcemia and no STX16 gene deletions. She had a mosaic karyotype of 46, X, del(X)(p11.4)/45, XO. Pyrosequencing was performed to determine the GNAS exon 1A methylation. The degree of methylation found in exon 1A of the patient was lower than her unaffected relatives. Abstract : Supplemental Digital Content is Available in the Text.